The Role of Social Media Marketing Activities to Improve E-Wom and Visit Intention to Indonesia Tourism Destinations through Brand Equity - Nabilla Dyah Eka Pramudhita; Putu Nina Madiawati (Akademi Sekretari Manajemen Taruna Bakti, 2021)
The development of technology that continues to grow, one of which is easy internet access enables people to access information from various sources, including social media. Nowadays, social media is not only used privately, but also companies and even government. One of them, the tourism sector in government. The role of social media, especially Instagram, is recognized as the most appropriate promotional media for travelers in Indonesia. Activities held on social media will spur the occurrence of e-wom and visit intention to Indonesian tourist destinations for domestic tourists. E-wom can be positive and negative e-wom. Therefore, the Indonesian Ministry of Tourism uses @Pesonaid_travel to promote Indonesian tourism and also the Pesona Indonesia’s brand used in @Pesonaid_travel. The purpose of this study is to determine the role of social media marketing activities to increase e-WoM and visit intention through brand equity. This research is a quantitative study, with the type of research used is causality. The population in this study was followers @Pesonaid_travel, totaling 276.000, which was then tested on 400 respondents, using a questionnaire. The data analysis method used is SEM which is processed with the SmartPLS application. The results of this study indicate that each variable that has an effect The results of this study indicate that every variable that exists gives a positive and significant effect on other variables.